An exploration of understandings and expectations around differentiation in mathematics, science and technology education - Cherub, Fauzia (Rhodes University, Faculty of Education, Department of Education, 2005)
The exploratory study presented in this thesis is a case study, interpretive in nature and located in the qualitative paradigm. The conceptual focus is on differentiation, recognizing that learners vary from one another and so will need educators to consider a wide range of factors to enable learners to learn. The objectives of the study are: "¢ To identify what Whole School Evaluation (WSE) supervisors understand by the term differentiation (conceptual) "¢ To identify how WSE supervisors expect differentiation to be achieved by educators (conceptual). [n order to contextualise this research, a further objective was considered necessary: "¢ To identify the roles of WSE supervisors (contextual) This was set in the context of mathematics, science and technology education. The study was carried out with a group of ten WSE supervisors who were involved in evaluating Mathematics, Science and or Technology education in the GET (General Education and Training) Band. Analysis of questionnaires and documents led to the identification of supervisory roles, while analysis of semi-structured interviews revealed a range of dimensions related to differentiation understandings and expectations. These dimensions have been developed into a typology which is then drawn upon in the development of a new conceptual model of differentiation, particularly relevant to the South African context. Findings presented in the study represent an attempt to understand and make recommendations related to policy, practice, research, curriculum and learning support material (LSM) development, training and evaluation. Textual layering in the form of reflective footnotes and issue boxes. plus specific reflective sections in the main text e.g. limitations and assumptions, help the text to achieve this goal. While the study was focused on the context of mathematics, science and technology education, it became apparent that the findings could be applied across all the learning areas.
Keywords: Education -- South Africa; Educational evaluation -- South Africa; Comparative education; Mathematics -- Study and teaching -- South Africa; Science -- Study and teaching -- South Africa; Technology -- Study and teaching -- South Africa; Education and state -- South Africa; Differentiation (Sociology); Competency-based education -- South Africa